KONSTRUKSI POSESIF BAHASA INDONESIA DALAM RUBRIK SURAT PEMBACA - Teguh Setiawan (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to describe characteristics of the relationship between the possessor and the possessed in Indonesian possessive constructions in letters to the editor. Theresearch data were sentences with possessive constructions collected from letters to theeditor in Kedaulatan Rakyat and Kompas daily newspapers in 2015. The data were collectedby reading and noting and were analyzed by means of the distributional method todetermine the possessive constructions and the correspondence method to determinethe relationships between the possessor and the possessed. The findings are as follows.First, the possessive constructions in letters to the editor are in the form of noun phraseswith two types of constructions, namely (1) Common Noun + Personal Pronoun, and (2)Common Noun + Proper Noun. Second, there are two types of relationships betweenthe possessor and the possessed in the possessive constructions, namely the kinshipand ownership relationships. The relationships can be categorized into two possessiverelationships, namely the lexical/inherent possessive relationship (kinship relationship)and the extrinsic possessive relationship (ownership relationship).